Association between Paediatric Complementary and Alternative Medicine Use and Parental Health Literacy, Child Health, and Socio-Economic Variables: A Prospective Study - Abida Denny; Andrew S. Day; Angharad Vernon-Roberts (MDPI AG, 2024)
Complementary and Alternative Medicines (CAMs) constitute products and practices not considered allopathic medicine. CAM use is high in children, but little is known about factors that may influence parents using CAM with their child. This study aimed to determine the variables associated with CAM use in children with a prospective study among children and their parents attending a tertiary care hospital in New Zealand (NZ). Outcomes included current CAM use, parental opinions on CAM, parental health literacy and child well-being. This study was completed by 130 parents (85% female), and the mean child age was 6.7 years. CAM use was reported for 59 (45%) children, the most common being oral supplements and body manipulation. Children were more likely to use CAM if their parent had higher health literacy (p = 0.001), and if they had previously attended the emergency department within 12 months (p = 0.03). There was no association between child well-being and CAM use. Parental opinion of using CAM only if a doctor recommended it was associated with CAM use for their child (p = 0.01). Only 40% of parents disclosed their child's CAM use to the medical team. This study highlights that parental health literacy influences the use of CAM for children in NZ, providing insight for translational research to improve CAM safety and disclosure rates in NZ.